Network-Induced Agency Conflicts in Delegated Portfolio Management - Gao, Xinzi; Wong, T. J.; Xia, Lijun; Yu, Gwen (The Accounting Review, 2021)
ABSTRACT Social ties between mutual funds and the companies in which they invest (investees) can both facilitate information transfers and encourage favoritism. Using the investment choices of mutual funds in China, we compare investment performance of holdings in companies that are socially connected to mutual funds versus those that are not. We find that funds allocate more investment to connected investees' stocks, especially when a fund is weakly monitored. This overweighting is greater in times of poor investee performance, when the benefits of additional investment to the connected investees are high. Weakly monitored funds' preference for connected stocks hurts the returns of these funds, yielding a 6.6 percent lower annualized risk-adjusted return, relative to closely monitored funds. These results suggest that, absent sufficient monitoring, agency conflicts generated by social networks can dominate the information advantages of these networks. JEL Classifications: G10; G11; G14.